“Jungle Quest” Edukasi Pengetahuan Umum Lima Binatang Langka Indonesia Dalam Permainan Kartu - Hizkia Kurniawijaya Hanz; Samuel Gandang Gunanto; Pandan Pareanom Purwacandra (Institut Seni Indonesia Yogyakarta, 2019)
In this era of digital games, card games are quite difficult to find markets, because they have issue, and the production costs are not small. Compared to digital games that only need to be downloaded from the store application and can be played anywhere without spending a lot of money even free.According to the boardgame community data on the boardgame.id website, the number of enthusiastic boardgame players in Indonesia in 2017 is increasing because more and more indie developers are starting to create board games with interesting and creative ideas, which can attract board game enthusiasts to try and playBased on these data, the author plans a card game that can be played by certain people with the education theme of Indonesian rare animal information. Searching for Forests, among others, provides information about the general knowledge of five rare Indonesian animals, while training players’ dexterity.Keywords: Cardgame, Game, Jungle Quest